Surgical versus percutaneous multivessel coronary revascularization in patients with chronic kidney disease. (6th December 2019) - Kilic, Arman; Sultan, Ibrahim; Gleason, Thomas G; Wang, Yisi; Smith, Conrad; Marroquin, Oscar C; Thoma, Floyd; Toma, Catalin; Lee, Joon S; Mulukutla, Suresh R
Abstract: OBJECTIVES: This study compared contemporary outcomes following surgical versus percutaneous coronary revascularization for multivessel coronary artery disease (MVCAD) in patients with chronic kidney disease. METHODS: Patients with MVCAD and a reduced glomerular filtration rate (<60 ml/min) undergoing coronary bypass surgery (CABG) or percutaneous coronary intervention (PCI) at a single institution between 2010 and 2017 were included. The primary outcome was major adverse cardiac and cerebrovascular events (MACCE) defined as a composite outcome of death, stroke, myocardial infarction or repeat revascularization. Multivariable Cox regression models were used for risk-adjustment and propensity matching was also performed. RESULTS: A total of 1853 patients were included in the study (1269 CABG, 584 PCI). CABG was associated with greater 5-year freedom from MACCE (70.1% vs 47.3%, P < 0.0001), a finding that persisted after risk-adjustment. The rates of early and late mortality and readmission were also lower with CABG as were individual rates of myocardial infarction and repeat revascularization. A propensity-matched analysis generated 704 well-matched patients (352 in each arm) with similar results, including greater 5-year freedom from MACCE (72.8% vs 45.8%, P < 0.0001), improved 5-year survival (73.9% vs 52.3%, P < 0.0001), lower readmission (cause-specific hazard ratio 0.68, 95% confidence interval 0.58–0.80; P < 0.0001), lower individual rates of myocardial infarction (2.6% vs 9.7%, P < 0.0001) and repeat revascularization (1.1% vs 7.4%, P < 0.0001). CONCLUSIONS: CABG is associated with a lower MACCE rate than that of PCI in patients with MVCAD and chronic kidney disease. Multidisciplinary discussions regarding the optimal revascularization strategy are important in MVCAD, particularly in more complex scenarios such as chronic kidney disease.